Perbandingan Tindak Pidana Pemerkosaan dan Komparasi Sanksi pada KUHP Lama dan KUHP Baru di Indonesia - Rahmah, Siti; Tia Juliana; Besse Dina Maria Oktavia; Nur ayiyin; Feni Puspitasari (AL-BAHTS: Jurnal Ilmu Sosial,Politik, dah Hukum, 2025)
Criminal acts against morality such as molestation and rape are often equated by the general public who do not understand their classification, even though legally, they are two different types of crimes. The main differences are seen in the object of violence, the elements of the act, and the determination of punishment for the perpetrator. This study aims to analyze, compare, and identify differences in the regulation of rape in the old Criminal Code (KUHP), which is a legacy of the colonial era and is regulated in Articles 285 to 288, with the new Criminal Code enacted through Law Number 1 of 2023, specifically Article 475. This research method uses a normative juridical approach with a focus on positive law. The results show that the key differences in rape between the old and new Criminal Code lie in the elements of the act and coercion that are more detailed regulated in the new Criminal Code, as well as differences in the definition of rape and increased sanctions for perpetrators. The new Criminal Code shows an increase in harsher penalties through increases in minimum and maximum penalties, as well as the introduction of additional penalties. This article concludes that the old and new Criminal Codes have significant differences in their views on the criminal acts of rape and indecency, as well as in the increased sanctions for perpetrators.